onnonal assay in repeat breeding cows and buffaloes - VENKATESAN, P S; SHANKAR, M SHYAM; SUBRAMANIAN, A (The Indian Journal of Animal Reproduction, 2005)
A study was conducted to assess the hormonal status in 70 repeat breeder and 14 regular breeder cows and buffaloes in Chennai, Tamilnadu. Circulating progesterone level was higher on day 0 and lower on day 7 in repeat breeder than in regular breeder. Estrogen level was lower on day 0 and day 7 in repeat breeder than regular breeder cows and buffaloes. Regular breeder cows had a significant higher level of T3 and T4 on day 0 than the repeat breeder cows and buffaloes. It is concluded from the study that this difference in hormonal concentration of repeat breeders from regular breeders might be resJf<>nsible for the reproductive disorders in cows and buffaloes.